Nanogels as Pharmaceutical Carriers: Finite Networks of Infinite Capabilities - Kabanov, Alexander V. (2009)
Nanogels are swollen nano-sized networks composed of hydrophilic or amphiphilic polymer chains, which can be non-ionic or ionic. They are developed as carriers for drug delivery and can be designed to spontaneously absorb biologically active molecules through formation of salt bonds, hydrogen bonds, or hydrophobic interactions. Polyelectrolyte nanogels can readily incorporate oppositely charged low molecular mass drugs or biomacromolecules such as oligonucleotides, siRNA, DNA and proteins, which bind with the nanogel ionic chains and phase separate within the finite nanogel volume. As a result, the loading capacity of such nanogels is superior to most other drug carriers. Binding of the drugs induces collapse of nanogel, which usually decreases the volume by at least one order of magnitude. However, the drug-nanogel particles remain dispersed due to the lyophilizing effect of nanogel’s hydrophilic polymer chains, such as poly(ethylene glycol) exposed at the particle surface. Multiple chemical functionalities of nanogels can be employed for introduction of imaging labels, targeting molecules and triggered drug release capabilities such as stimuli-responsive and degradable cross-links. Recent studies suggested several promising biomedical applications of nanogels, including drug delivery of phosphorylated nucleoside analogs, oligonucleotides or siRNA for anticancer or antiviral treatment, encapsulation of bioactive proteins, fabrication of nanometallic or nanoceramic composites, imaging agents, oral and CNS drug delivery. The research of different functional nanogels as novel pharmaceutical carriers for diagnosis and therapy shows promise and is rapidly developing.